Analysis of The Factors Affecting Understanding of Small and Medium Businesses in Preparing Financial Reports - Wibowo, Adi; Panday, Rorim; Mardiyah, Siti; Prasetyo, Arif (Journal of Entrepreneurship, Business and Economics; Vol 6 No 2 (2018), 2019)
This research analyzes the information and influence factors of socialization, size of the business, as well as the perceptions of entrepreneurs of Small Medium Enterprises to understanding in preparing of the financial statements accordance Accounting Standards for Entities without Public Accountability. The object of research are the Wedding Organizer entrepreneurs in Bekasi City. This research using quantitative research methods with sample as 75 units of Small Medium Enterprises . Multiple regression will be used to analyze. T test results showed partially on information and dissemination as well as influence business size significantly, while perceptions of owners do not influence on the understanding of Small Medium Enterprises about Accounting Standards for Entities without Public Accountability (ASEPA). As simultaneously all independent variables effect on the dependent variable.This research suggests that by improving their understanding in preparing of financial report can provide opportunities for Small Medium Enterprises entrepreneurs to apply for loans to third parties in developing their businesses. Research paper Keywords: Information, Socialization, Business size, Owner's perception, Financial statements Reference to this paper should be made as follows: Wibowo, A., Pandey, R., Mardiyah, S., & Prasetyo, A. (2018). Analysis of The Factors Affecting Understanding of Small and Medium Businesses in Preparing Financial Reports, Journal of Entrepreneurship, Business and Economics , 6 (2), 91–100.